Hole blocking PbI2/CH3NH3PbI3 interface. Issue 9 (16th July 2014) - Somsongkul, Voranuch; Lang, Felix; Jeong, Ah Reum; Rusu, Marin; Arunchaiya, Marisa; Dittrich, Thomas
Abstract : Modulated charge separation across (MO)/CH3 NH3 PbI3 and (MO)/PbI2 /CH3 NH3 PbI3 (MO = TiO2, MoO3 ) interfaces was investigated by surface photovoltage (SPV) spectroscopy. Perovskite layers were deposited by solution‐based one‐step preparation and two‐step preparation methods. An unreacted PbI2 layer remained at the interface between the metal oxide and CH3 NH3 PbI3 for two‐step preparation. For the two‐step preparation on TiO2, the SPV signal related to absorption in CH3 NH3 PbI3 increased in comparison to the one‐step preparation due to electron transfer from CH3 NH3 PbI3 via PbI2 into TiO2 whereas the SPV signal related to defect transitions decreased. For the one‐step preparation on MoO3, holes photogenerated in CH3 NH3 PbI3 recombined with electrons in MoO3 . In contrast, a hole transfer from CH3 NH3 PbI3 towards MoO3 was blocked by the PbI2 interlayer for the two‐step preparation on MoO3 . (© 2014 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : Electrons photogenerated in CH3 NH3 PbI3 are injected into TiO2 via a PbI2 passivating buffer layer. In contrast, the transfer of photogenerated holes into MoO3 via PbI2 is blocked. The conduction band edges of PbI2 and CH3 NH3 PbI3 are well aligned whereas the valence band offset is of the order of 0.8 eV.